Assessment of the Correlation Between Vitamin D and T3, T4, FT3, FT4 and TSH Among Patients with Graves' Disease - Angham Jasim Mohammed Ali, Majedaldeen Jumaa Majeed Hamoud, (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Graves' disease is characterized by a diffuse hyperfunctional goiter that develops suddenly and is linked to an immune thyroid stimulating factor. Graves' disease hyperthyroidism is caused by circulating IgG antibodies binding to and activating the G-protein–coupled thyrotropin receptor. This activation causes thyroid enlargement by stimulating follicular hypertrophy and hyperplasia, as well as increases in thyroid hormone synthesis. Objectives: This study aims to assess the Determination the concentration of vitamin D in patients with graves diseases, Measurement T3, T4, FT3, FT4 and TSH hormones and Determination the correlation between immunological markers by the (SPSS). Materials and Methods: This research included a total of (90) people of various sexes and ages (30 men and 60 females), including (60) Graves' disease patients and (30) healthy people. Patients with Graves' disease were seen at Alsader Medical City (Najaf Center for Diabetes and Endocrinology). Between November 2021 and January 2022. Results: In this research, the levels of (T3, T4, TSH, FT3 and FT4) hormones and Vitamin D revealed a very significant association (P.value> 0.005) across the groups tested. A non-significant association was also found between vitamin D and other variables. According to the patients' group, the FT3 revealed a strong negative connection with vitamin D in comparison to the other parameters. Conclusion: The Thyrotropin receptor antibody (TRAb) test and ultrasonography of the thyroid gland are useful diagnostic tools for autoimmune Graves' disease. Grave's disease is connected with decreased vitamin D levels in the blood and could be made worse by high serum levels of T3, T4, FT3, FT4, and TRAb-positive and a low serum level of TSH.